Local Morphine Withdrawal Increases c-fos Gene, Fos Protein, and Oxytocin Gene Expression in Hypothalamic Magnocellular Neurosecretory Cells - Johnstone, Louise E. (J Neurosci, 2000)
We measured stimulation of c-fos and oxytocin gene expression during excitation of oxytocin cells induced by systemic or local morphine withdrawal. Female rats were made morphine-dependent by intracerebroventricular morphine infusion over 5 d. Morphine withdrawal, induced by systemic injection of the opioid antagonist naloxone (5 mg/kg) in conscious or anesthetized rats, increased the density of c-fos messenger RNA and of oxytocin heterogeneous nuclear RNA in supraoptic nucleus cells compared with those of nonwithdrawn rats; c-fos messenger RNA was also increased in the magnocellular and parvocellular paraventricular nuclei of withdrawn rats. Morphine withdrawal increased the number of Fos-immunoreactive cells in the supraoptic and magnocellular paraventricular nuclei of conscious or pentobarbitone-anesthetized rats. Morphine withdrawal also increased Fos-immunoreactive cell numbers in the parvocellular paraventricular nucleus of conscious but not anesthetized rats. Central administration of the α(1)-adrenoreceptor antagonist benoxathian (5 μg/min) did not prevent morphine withdrawal-induced increases in the numbers of Fos-immunoreactive neurons in the supraoptic or magnocellular paraventricular nucleus. Unilateral microdialysis administration of naloxone (10(−5)m) into the supraoptic nucleus of anesthetized morphine-dependent rats increased Fos-immunoreactive cell numbers compared with the contralateral nucleus. Finally, we investigated whether dependence could be induced by chronic unilateral infusion of morphine into a supraoptic nucleus; systemic naloxone (5 mg/kg) increased Fos-immunoreactive cell numbers in the morphine-infused nucleus compared with the contralateral nucleus. Thus, morphine withdrawal excitation increases c-fos and oxytocin gene expression in supraoptic nucleus neurons. This occurs independently from excitation of their ascending noradrenergic inputs, and both dependence and withdrawal can be induced within the supraoptic nucleus.